2016
DOI: 10.1093/mnras/stw1328
|View full text |Cite|
|
Sign up to set email alerts
|

A burst in a wind bubble and the impact on baryonic ejecta: high-energy gamma-ray flashes and afterglows from fast radio bursts and pulsar-driven supernova remnants

Abstract: Tenuous wind bubbles, which are formed by the spin-down activity of central compact remnants, are relevant in some models of fast radio bursts (FRBs) and superluminous supernovae. We study their high-energy signatures, focusing on the role of pair-enriched bubbles produced by young magnetars, rapidly-rotating neutron stars, and magnetized white dwarfs. (i) First, we study the nebular properties and the conditions allowing for escape of high-energy gamma-rays and radio waves, showing that their escape is possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
285
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(310 citation statements)
references
References 109 publications
(157 reference statements)
23
285
1
1
Order By: Relevance
“…Marcote et al (2017) have shown that the bursts and the persistent radio source are co-located to within a linear projected separation of 40 pc, suggesting that the two emission sources should be physically related, though not necessarily the same source. The radio source properties are consistent with a low-luminosity AGN or a young (<1000 year) supernova remnant (SNR) powered by an energetic neutron star (e.g., Murase et al 2016).…”
Section: ( ) ( )mentioning
confidence: 65%
“…Marcote et al (2017) have shown that the bursts and the persistent radio source are co-located to within a linear projected separation of 40 pc, suggesting that the two emission sources should be physically related, though not necessarily the same source. The radio source properties are consistent with a low-luminosity AGN or a young (<1000 year) supernova remnant (SNR) powered by an energetic neutron star (e.g., Murase et al 2016).…”
Section: ( ) ( )mentioning
confidence: 65%
“…Lorimer et al 2007;Keane et al 2012;Thornton et al 2013;Deng & Zhang 2014;Gao et al 2014;Murase et al 2016a), i.e.…”
Section: Methodsunclassified
“…However, neither the SFR of M 240 1000 yr 1 - -nor the size of the region of 250-360 pc of Arp220 (Anantharamaiah et al 2000) agrees with the properties of the persistent source associated with FRB121102 ( M 0.4 yr 1 - and 0.7 pc  ). Murase et al (2016) and Piro (2016) discuss the properties of a young ( 1000 years < ) SNR that is powered by the spin-down power of a neutron star or white dwarf. The SNR expands into the surrounding medium and evacuates an ionized region that can be seen as a luminous synchrotron nebula.…”
Section: Young Neutron Star and Nebulamentioning
confidence: 99%